Information Technology and Public Sector Corruption - RICHARD HEEKS (Working Paper Series Paper No. 4, 1998)
Corruption is a major problem for many parts of the public sector. One dominant vision of corruption restraint - the `Panoptic vision' - sees information technology (IT) as a key enabler of management control. This paper presents five short case studies of IT and public sector corruption to test the realities of this Panoptic vision. From these it is concluded that, while IT sometimes does detect and remove corruption, it can also have no effect or even provide new corruption opportunities for some public servants. Management of corruption is ultimately shaped more by management decisions and by broader organisational and environmental factors than it is by technology. Put simply, IT-based systems guided by the Panoptic vision affect symptoms of a corrupt system rather than causes. Public managers must therefore adopt a more holistic vision of corruption control. They must also recognise the link between IT and corruption in the planning of some public sector information systems.